Howards End [videorecording (DVD)] - Forster, E. M. (Edward Morgan), 1879-1970 (PBS, 2020)
The show follows Margaret and Helen Schlegel, two intelligent, idealistic sisters living together in Edwardian London with their hypochondriac brother, Tibby. Their loving but interfering Aunt Juley tries to keep the siblings in line after the death of their parents, but a series of events push the sisters to lead unorthodox lives full of romance, tragedy, and drama.